Secondary battery and electric device
By providing a thicker ceramic layer at the starting end portion of the first diaphragm winding of the secondary battery and a fourth ceramic layer at the second part, the problem of the electrode assembly separator being easily pierced and causing short circuits is solved, and the safety performance and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202411803080.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In secondary batteries, the diaphragm near the start of winding of the electrode assembly is easily pierced, resulting in short circuits, and poor high-voltage insulation test results and K value.
By providing a thicker first ceramic layer at the winding starting end portion of the first diaphragm, the structural strength is improved, the case of insufficient electrolyte is reduced, and a fourth ceramic layer is provided in the second portion to improve the puncture resistance strength.
The possibility of short circuit caused by direct contact between the first pole sheet and the second pole sheet is effectively reduced, the Hipot test results and K value are improved, and the safety performance and circulation performance of the secondary battery are improved.
Smart Images

Figure CN119581692A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] In secondary batteries, the closer the electrode assembly is to the start of winding, the greater the winding pressure it is subjected to. Li-Co particles, carbon powder, etc. are easily dropped on the inner ring of the diaphragm, squeezing the diaphragm, which makes the diaphragm easy to be punctured, and the pole pieces of different polarities are directly in contact and short-circuited, and the Hi-pot test (High Potential test, high-voltage insulation test) results and K value (the voltage drop of the battery per unit time, which is an indicator used to measure the self-discharge rate of lithium batteries) are significantly deteriorated. Summary of the invention
[0003] In view of this, it is necessary to provide a secondary battery that can improve the puncture resistance of the diaphragm and reduce the possibility of short circuit of the electrode assembly.
[0004] An embodiment of the first aspect of the present application provides a secondary battery, the secondary battery comprising an electrode assembly, the electrode assembly comprising a first electrode sheet, a second electrode sheet and a first diaphragm, the first electrode sheet, the first diaphragm and the second electrode sheet are sequentially stacked to form a winding structure; along the winding direction of the first diaphragm, the first diaphragm comprises a first part and a second part arranged sequentially, and compared with the second part, the first part is close to the winding starting end of the winding structure; along the thickness direction of the first diaphragm, the first part comprises a first ceramic layer and a first base film arranged in a stacked manner, and the second part comprises a second ceramic layer and a second base film arranged in a stacked manner; the first electrode sheet comprises a first current collector and a first pole ear, the first pole ear is connected to the first current collector and extends from one side in the width direction of the first current collector; the first ceramic layer comprises a first region and a second region sequentially arranged along the width direction of the first diaphragm; when viewed along the thickness direction of the first diaphragm, part of the first pole ear overlaps part of the first region; the thickness of the first region is H 1 , the thickness of the second region is H 2 , the thickness of the second ceramic layer is H 3 , 2μm≤H 2 ≤10μm, 0≤H 1 / H 2 ≤1, and 1.2≤H 2 / H 3 ≤10.
[0005] In the secondary battery described above, the thickness H of the second region in the first ceramic layer near the winding start end of the winding structure is 2 Set to 2μm≤H 2≤10μm, which is conducive to improving the structural strength of the first part of the first diaphragm near the starting end of the winding, making the first part less likely to be punctured, thereby reducing the possibility of short circuit caused by direct contact between the first pole piece and the second pole piece. In addition, the ceramic material in the first ceramic layer has pores, which is conducive to storing electrolyte. By setting a thicker first ceramic layer in the first part, the electrolyte can easily penetrate into the center of the winding, reducing the situation of insufficient electrolyte near the center of the winding. By making 1.2≤H 2 / H 3 ≤10, that is, the thickness H of the second area near the winding start end of the winding structure 2 Than the thickness H of the second ceramic layer away from the winding start end 3 The first ceramic layer can be made thick enough to provide the first part with sufficient puncture resistance, improve the problem of insufficient electrolyte in the winding center, and reduce the loss of secondary battery volume energy density caused by thickening the ceramic layer on the entire first diaphragm; at the same time, the thickness difference between the first part and the second part can be made not too large to reduce the impact on the secondary battery volume energy density and the flatness of the electrode assembly. Because the first pole piece includes a first pole ear, the setting of the first pole ear will increase the thickness of the position, so the thickness of the first area overlapping with the first pole ear is set to be less than the thickness of the second area, which can reduce the loss of secondary battery volume energy density caused by the superposition of the thickness of the first pole ear.
[0006] In one or more of the above embodiments, 1.5≤H 2 / H 3 ≤5.
[0007] In the above embodiment, H 2 / H 3 Within the above range, the puncture resistance of the first portion can be further improved and the problem of insufficient electrolyte in the winding center can be improved, while taking into account both the volume energy density of the secondary battery and the flatness of the electrode assembly.
[0008] In one or more of the above embodiments, 0.2≤H 1 / H 2 ≤0.5.
[0009] In the above embodiment, H 1 / H 2 Within the above range, a ceramic layer of a certain thickness is also provided on the first region to improve the electrolyte infiltration near the first electrode tab, and H 1 / H 2 ≤0.5, so that there is a certain thickness difference between the first area and the second area, reducing the excessive thickness at the position of the first pole ear caused by the superposition of the thickness of the first pole ear and the ceramic layer, thereby reducing the loss of volume energy density of the secondary battery.
[0010] In the above embodiment, by setting H 1 =H 3 , which can simplify the manufacturing process of the first diaphragm.
[0011] In one or more of the above embodiments, 0.3 μm ≤ H 3 ≤1.5μm.
[0012] In the above embodiment, when the above range is met, the thickness of the second part can be kept from increasing too much while the structural strength of the second part is improved, thereby reducing the impact on the volume energy density of the secondary battery.
[0013] In one or more of the above embodiments, 2 μm ≤ H 2 ≤3μm.
[0014] In the above embodiment, H 2 When the above range is met, the puncture resistance of the first part can be enhanced while reducing the influence of the thickness of the first ceramic layer and the thickness of the electrode assembly after winding, thereby reducing the loss of volume energy density of the secondary battery.
[0015] In one or more of the above embodiments, the first membrane includes a multi-fold membrane segment, and the first part includes N fold membrane segments located at the starting end of the winding, 1≤N≤15.
[0016] In the above embodiment, the winding structure is subjected to a greater winding pressure near the starting end of the winding. By thickening the thickness of the first ceramic layer in the first part near the starting end of the winding, the puncture resistance of the first diaphragm in this part can be improved, and the electrolyte infiltration degree of the electrode assembly near the winding center can be improved, so that the electrode assembly near the winding center is not easy to precipitate lithium, and the cycle performance of the secondary battery is improved. If N is too small, the first part is not enough to improve the overall strength of the first diaphragm, the improvement of the puncture resistance of the first diaphragm is small, and the electrolyte is difficult to infiltrate to the middle position of the electrode assembly; if N is too large, the first part has a greater impact on the overall thickness of the electrode assembly, and the volume energy density of the secondary battery is lost more.
[0017] In one or more of the above embodiments, 2≤N≤7.
[0018] In the above embodiment, the overall thickness of the electrode assembly can be further reduced while increasing the puncture resistance of the first separator near the winding start end, improving the electrolyte infiltration effect on the electrode assembly, and reducing the risk of lithium plating.
[0019] In one or more of the above embodiments, along the width direction of the first pole piece, the width of the first region is W 1 , 10mm≤W 1 ≤30mm.
[0020] In the above embodiment, when the width of the first area is too large, the width of the second area will become narrower, and the thickened part will become narrower, which makes the thickened area of the first part smaller, which is not conducive to reducing the risk of the first part being punctured. If the width of the first area is too small, the first pole ear is easy to overlap with the second area, thereby increasing the thickness of the electrode assembly after winding, resulting in a loss of volume energy density of the secondary battery. Satisfying 10mm≤W 1 When the thickness of the electrode assembly is ≤30 mm, the second area can be enlarged as much as possible without increasing the thickness of the electrode assembly, thereby reducing the risk of the first portion being punctured and improving the safety performance of the secondary battery.
[0021] In one or more of the above embodiments, the materials of the first ceramic layer and the second ceramic layer each independently include at least one of aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, barium titanate, and boehmite.
[0022] In the above embodiments, alumina, silica, titanium dioxide, zirconium oxide, barium titanate and boehmite have good mechanical strength, high hardness and compressive resistance, which is conducive to preventing the first diaphragm from being punctured by impurities such as particles and powders, thereby improving the safety of the secondary battery.
[0023] The embodiment of the second aspect of the present application provides a secondary battery, the secondary battery comprising an electrode assembly, the electrode assembly comprising a first electrode sheet, a second electrode sheet and a first diaphragm, the first electrode sheet, the first diaphragm and the second electrode sheet are sequentially stacked to form a winding structure; the first electrode sheet comprises a first current collector and a first electrode ear, the first electrode ear is connected to the first current collector and extends from one side in the width direction of the first current collector; along the width direction of the first diaphragm, the first diaphragm comprises a third part and a fourth part arranged in sequence; observed along the thickness direction of the first diaphragm, part of the first electrode ear overlaps part of the third part; the third part comprises a third base film, and the fourth part comprises a fourth ceramic layer and a fourth base film stacked along the thickness direction of the first diaphragm; the thickness of the third part is H 4 , the thickness of the fourth part is H 5 , H 4 <H 5 ; The thickness of the fourth ceramic layer is H 7 , 2μm≤H 7 ≤10μm.
[0024] In the above-mentioned secondary battery, a fourth ceramic layer is provided in the fourth portion and the thickness of the fourth ceramic layer is 2 μm to 10 μm. The fourth ceramic layer has good mechanical strength, which is beneficial to reduce the possibility of the first diaphragm being punctured and the risk of short circuit caused by direct contact between the first pole piece and the second pole piece. In addition, the thickness H of the third portion overlapping with the first pole ear is 4 Less than the thickness H of the fourth portion 5, which can reduce the thickness of the electrode assembly after winding, and is beneficial to reducing the loss of volume energy density of the secondary battery.
[0025] In one or more of the above embodiments, along the width direction of the first pole piece, the width of the third portion is W 2 , 10mm≤W 2 ≤30mm.
[0026] In the above embodiment, the width W of the third portion is 2 If the width of the third part is too small, the first pole ear is easy to overlap with the fourth ceramic layer of the fourth part, which increases the thickness of the electrode assembly after winding and causes the loss of volume energy density of the secondary battery. 2 When the thickness of the electrode assembly is ≤30 mm, the fourth portion can be enlarged as much as possible without increasing the thickness of the electrode assembly, thereby reducing the risk of the first portion being punctured and improving the safety performance of the secondary battery.
[0027] In one or more of the above embodiments, the third part further includes a third ceramic layer, the third ceramic layer and the third base film are stacked along the thickness direction of the first diaphragm, and the thickness of the third ceramic layer is H. 6 , the thickness of the fourth ceramic layer is H 7 , 0.2≤H 6 / H 7 ≤0.5.
[0028] In the above embodiment, the third ceramic layer is provided to improve the electrolyte infiltration near the first electrode tab and meet the requirements of H 6 / H 7 When ≤0.5, the thickness overlap of the first electrode tab and the third ceramic layer can be reduced, and the thickness increase of the electrode assembly after winding can be reduced, which is beneficial to reducing the volume energy density loss of the secondary battery.
[0029] In one or more of the above embodiments, 0.3 μm ≤ H 6 ≤1.5μm.
[0030] In the above embodiment, when the above range is met, the thickness of the fourth part is not likely to increase too much while improving the structural strength of the fourth part, thereby reducing the impact on the volume energy density of the secondary battery.
[0031] In one or more of the above embodiments, 2 μm ≤ H 7 ≤3μm.
[0032] In the above embodiment, 2μm≤H 7When the thickness of the fourth ceramic layer is ≤3 μm, the thickness of the fourth ceramic layer can be made greater than that of the third ceramic layer, while the thickness of the fourth ceramic layer is not easily made too large, thereby reducing the impact on the overall thickness of the electrode assembly.
[0033] An embodiment of a third aspect of the present application provides an electrical device, comprising the secondary battery in any of the above embodiments.
[0034] In the above-mentioned electrical device, by thickening the thickness of the first diaphragm in some areas, the first diaphragm is not easily punctured, so that the first electrode plate is not easily short-circuited with the second electrode plate, thereby improving the safety of the secondary battery and further improving the safety of the electrical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a three-dimensional diagram of a secondary battery in one embodiment of the present application.
[0036] Figure 2 yes Figure 1 Cross-sectional view along the Ⅱ-Ⅱ direction.
[0037] Figure 3 yes Figure 2 Enlarged view of part III.
[0038] Figure 4 yes Figure 2 Schematic diagram of the structure of the diaphragm.
[0039] Figure 5 It is a partial cross-sectional view of the first diaphragm after expansion in one embodiment of the present application.
[0040] Figure 6 It is a partial top view of the first diaphragm after expansion in one embodiment of the present application.
[0041] Figure 7 It is a partial cross-sectional view of the first diaphragm after expansion in one embodiment of the present application.
[0042] Figure 8 is a partial cross-sectional view of an electrode assembly in one embodiment of the present application.
[0043] Fig. 9 It is a partial top view of the first diaphragm after expansion in one embodiment of the present application.
[0044] Fig.10 It is a partial cross-sectional view of the first diaphragm after expansion in one embodiment of the present application.
[0045] Fig.11 It is a partial cross-sectional view of the first diaphragm after expansion in one embodiment of the present application.
[0046] Fig.12It is a schematic diagram of the structure of an electrical device in an embodiment of the present application.
[0047] Main component symbols
[0048] 1000. Electric device; 100. Secondary battery; 10. Electrode assembly;
[0049] 11. first pole piece; 111. first current collector; 112. first active material layer; 113. first pole ear;
[0050] 12. second pole piece; 121. second current collector; 122. second active material layer; 123. second pole ear;
[0051] 13, diaphragm; 13a, first diaphragm; 131, first part; 1311, first basement membrane;
[0052] 1312, first ceramic layer; 1312a, first region; 1312b, second region; 132, second portion;
[0053] 1321, second base film; 1322, second ceramic layer; 133, first adhesive layer; 134, third part;
[0054] 1341, third base film; 1342, third ceramic layer; 135, fourth part; 1351, fourth base film;
[0055] 1352, fourth ceramic layer; 13b, second diaphragm; 13c, diaphragm segment; 10a, starting end;
[0056] 10b, tail end; 101, main body area; 1011, straight section; 102, corner area;
[0057] 1021. bending section; 20. shell; 200. device body.
[0058] The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0059] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0061] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0062] It should be noted that the thickness, length, width and other dimensions of various components in the embodiments of the present application shown in the drawings are only exemplary and should not constitute any limitation to the present application.
[0063] In secondary batteries, the closer the electrode assembly is to the winding center, the greater the winding pressure it is subjected to. Li-Co particles, carbon powder, etc. are easily dropped on the diaphragm of the inner circle of the winding structure, which squeezes the diaphragm, causing the diaphragm to be easily punctured, and the electrodes of different polarities directly contact and short-circuit, which greatly deteriorates the Hi-pot test results and K value.
[0064] An embodiment of the present application provides a secondary battery, the secondary battery comprising an electrode assembly, the electrode assembly comprising a first electrode sheet, a second electrode sheet and a first diaphragm, the first electrode sheet, the first diaphragm and the second electrode sheet are sequentially stacked to form a winding structure; along the winding direction of the first diaphragm, the first diaphragm comprises a first part and a second part arranged sequentially, and compared with the second part, the first part is closer to the winding starting end of the winding structure; along the thickness direction of the first diaphragm, the first part comprises a first ceramic layer and a first base film arranged in a stacked manner, and the second part comprises a second ceramic layer and a second base film arranged in a stacked manner; the first electrode sheet comprises a first pole ear, the first pole ear is connected to the first current collector and extends from one side in the width direction of the first electrode sheet; the first ceramic layer comprises a first region and a second region arranged sequentially along the width direction of the first electrode sheet; along the thickness direction of the first diaphragm, a part of the first pole ear overlaps a part of the first region; the thickness of the first region is H 1 , the thickness of the second region is H 2 , the thickness of the second ceramic layer is H 3 , 0≤H 1 / H 2 ≤1, and 1.2≤H 2 / H 3 ≤10.
[0065] In the secondary battery described above, the thickness H of the second region in the first ceramic layer near the winding start end of the winding structure is 2 Set to be thicker than the thickness H of the second ceramic layer away from the winding start end 3The first diaphragm is large, which is conducive to improving the structural strength of the first part near the winding start end, making the first part less likely to be punctured, thereby reducing the possibility of short circuit caused by direct contact between the first pole piece and the second pole piece. In addition, the ceramic material in the first ceramic layer has pores, which is conducive to storing electrolyte. By setting a thicker first ceramic layer in the first part, the electrolyte is easy to infiltrate into the winding center, reducing the situation of insufficient electrolyte near the winding center. By making 1.2≤H 2 / H 3 ≤10, which can not only make the first ceramic layer have a certain thickness to provide the first part with sufficient puncture resistance, but also improve the problem of insufficient electrolyte in the winding center, and make the thickness difference between the first part and the second part not too large, so as to reduce the impact on the volume energy density of the secondary battery and the flatness of the electrode assembly. Because the first pole piece includes the first pole ear, the setting of the first pole ear will increase the thickness of the position, so the thickness of the first area overlapping with the first pole ear is set to be less than the thickness of the second area, which can reduce the loss of the volume energy density of the secondary battery caused by the superposition of the thickness of the first pole ear.
[0066] The embodiments of the present application are further described below in conjunction with the accompanying drawings.
[0067] like Figure 1 and Figure 2 As shown, an embodiment of the present application provides a secondary battery 100, which includes an electrode assembly 10 and a housing 20, wherein the electrode assembly 10 is accommodated in the housing 20. The electrode assembly 10 includes a first pole piece 11, a second pole piece 12, and a diaphragm 13, wherein the diaphragm 13 is disposed between the first pole piece 11 and the second pole piece 12, and the diaphragm 13 is used to isolate the first pole piece 11 from the second pole piece 12.
[0068] In some embodiments, the housing 20 is a flexible packaging bag, such as an aluminum-plastic film. In other embodiments, the housing 20 is a hard shell, such as a plastic shell, or a metal shell including at least one of a steel alloy, an aluminum alloy, and a copper alloy.
[0069] In some embodiments, an electrolyte (not shown) is injected into the housing 20 , and the electrolyte components include a solvent, an electrolyte salt, and an additive.
[0070] In some embodiments, the electrolyte salt includes at least one of an organic lithium salt or an inorganic lithium salt.
[0071] In some embodiments, the electrolyte salt is not limited to lithium hexafluorophosphate (LiPF 6 ), bis(trifluoromethanesulfonyl)imide lithium LiN (CF 3 SO 2 ) 2(LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO 2 F) 2 )(LiFSI), lithium hexafluorocesium oxide (LiCsF 6 ), lithium perchlorate (LiClO 4 ) or lithium trifluoromethanesulfonate (LiCF 3 SO 3 ) at least one of.
[0072] In some embodiments, the polarities of the first electrode 11 and the second electrode 12 are different. For example, the first electrode 11 is an anode electrode, and the second electrode 12 is a cathode electrode. For another example, the first electrode 11 is a cathode electrode, and the second electrode 12 is an anode electrode.
[0073] See also Figure 2 and Figure 3 In some embodiments, the first electrode sheet 11 includes a first current collector 111 and a first active material layer 112 , the first active material layer 112 is disposed on at least one surface of the first current collector 111 along the thickness direction of the first electrode sheet 11 , and the diaphragm 13 is disposed between the first active material layer 112 and the second electrode sheet 12 .
[0074] See also Figure 2 and Figure 3 In some embodiments, the first current collector 111 has two opposite surfaces along the thickness direction of the first electrode sheet 11. A first active material layer 112 is disposed on at least one surface of the first current collector 111, for example, the first active material layer 112 is disposed on both surfaces of the first current collector 111.
[0075] See also Figure 2 and Figure 3 In some embodiments, the second pole piece 12 includes a second current collector 121 and a second active material layer 122. Along the thickness direction of the second pole piece 12, the second current collector 121 has two oppositely disposed surfaces, and the second active material layer 122 is disposed on at least one surface of the second current collector 121, for example, the second active material layer 122 is disposed on both surfaces of the second current collector 121.
[0076] See also Figure 1 and Figure 2 In some embodiments, for the electrode assembly 10 with a wound structure, the first pole sheet 11 further includes a first pole tab 113 , which is disposed on one side of the first current collector 111 in the width direction, and is welded to the first current collector 111 .
[0077] In some embodiments, the second pole piece 12 further includes a second pole tab 123 . The second pole tab 123 is disposed on one side of the second current collector 121 in the width direction. The second pole tab 123 is welded to the second current collector 121 .
[0078] In some embodiments, the first electrode tab 113 and the second electrode tab 123 are disposed on the same side of the electrode assembly 10 .
[0079] Taking the first pole piece 11 as an anode pole piece and the second pole piece 12 as a cathode pole piece as an example, the first current collector 111 and the second current collector 121 can be metal layers. The material of the first current collector 111 can be at least one of copper, nickel, tantalum, titanium, etc., such as copper foil. The material of the second current collector 121 can be at least one of aluminum, nickel, tantalum, titanium, etc., such as aluminum foil.
[0080] Taking the first pole piece 11 as an anode pole piece and the second pole piece 12 as a cathode pole piece as an example, the first active material layer 112 includes an anode active material, and the anode active material may include at least one of graphite, hard carbon, soft carbon, silicon, silicon-oxygen material, silicon-carbon material, etc. The second active material layer 122 includes a cathode active material, and the cathode active material may include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese iron phosphate, or lithium manganese oxide, etc.
[0081] Taking the first pole piece 11 as an anode pole piece and the second pole piece 12 as a cathode pole piece as an example, the first pole ear 113 is an anode pole ear and the second pole ear 123 is a cathode pole ear. The material of the first pole ear 113 includes at least one of copper, nickel, copper-nickel alloy, nickel-chromium alloy, copper-plated nickel, nickel-plated copper, silver-plated copper, stainless steel (such as 304 stainless steel), etc.; the material of the second pole ear 123 includes at least one of aluminum, aluminum alloy, nickel, nickel-plated aluminum, silver-plated aluminum, etc.
[0082] See also Figure 2 and Figure 3 In some embodiments, the first pole piece 11, the diaphragm 13 and the second pole piece 12 are stacked and wound to form a winding structure.
[0083] For example, the diaphragm 13 includes a first diaphragm 13a, and the first pole piece 11, the first diaphragm 13a and the second pole piece 12 are sequentially stacked to form a winding structure. For another example, the diaphragm 13 also includes a second diaphragm 13b, and the first pole piece 11, the first diaphragm 13a, the second pole piece 12 and the second diaphragm 13b are sequentially stacked and wound to form a winding structure.
[0084] In some embodiments, the structure and material of the second diaphragm 13b are the same as those of the first diaphragm 13a.
[0085] In the related art, a portion of the first active material layer 112 on the first electrode sheet 11 is removed to expose a portion of the first current collector 111 to form an empty foil area, and the first electrode tab 113 is welded to the empty foil area.
[0086] Hipot test (High Potential test) refers to an insulation resistance test that tests the resistance between the anode tab and the cathode tab. It is used to detect whether there is a short circuit inside the battery cell, to pick out defective products with folded diaphragm 13 and particles piercing the diaphragm 13, and to avoid defective products with zero voltage and K value.
[0087] The K value refers to the voltage drop of the secondary battery 100 per unit time, and is used to reflect the internal short circuit condition of the secondary battery 100 .
[0088] See also Figure 2 , Figure 4 , Figure 5 and Figure 6 ,in Figure 5 is a cross-sectional view of the first diaphragm 13a when the first diaphragm 13a is unfolded and viewed along the width direction of the first diaphragm 13a. Figure 6 is a top view of the first diaphragm 13a when the first diaphragm 13a is unfolded and viewed along the thickness direction of the first diaphragm 13a. Figure 5 As shown, along the winding direction R of the first diaphragm 13a, the first diaphragm 13a includes a first portion 131 and a second portion 132 arranged in sequence, and the first portion 131 is closer to the winding start end 10a of the winding structure than the second portion 132. The first portion 131 includes a first ceramic layer 1312 and a first base film 1311 stacked along the thickness direction of the first diaphragm 13a, and the second portion 132 includes a second base film 1321 and a second ceramic layer 1322. Figure 5 Medium 1 It is used to indicate the boundary between the first part 131 and the second part 132. Figure 6 , wherein the first electrode sheet 11 includes a first current collector 111 and a first electrode tab 113, the first electrode tab 113 is arranged on one side of the first current collector 111 in the width direction, and the first ceramic layer 1312 includes a first region 1312a and a second region 1312b arranged in sequence along the width direction of the first diaphragm 13a. When viewed along the thickness direction of the first diaphragm 13a, part of the first electrode tab 113 overlaps part of the first region 1312a. The thickness of the first region 1312a is H 1 , the thickness of the second region 1312b is H 2 , the thickness of the second ceramic layer 1322 is H 3 .
[0089] In some embodiments, the materials of the first base film 1311 and the second base film 1321 independently include at least one of polyethylene, polypropylene, polyimide, polyamide, polysulfone, polyacrylonitrile, polyester, cellulose, polyphenylene sulfide, polyacrylate, polyethylene terephthalate, polyparaben, polyarylethersulfoneketone, aramid or aramid.
[0090] In some embodiments, the materials of the first ceramic layer 1312 and the second ceramic layer 1322 each independently include aluminum oxide (Al 2 O 3 ), silicon dioxide (SiO 2 ), titanium dioxide (TiO 2 ), zirconium oxide (ZrO 2 ), barium titanate (BaTiO 3 ), boehmite (AlOOH) or at least one of the following.
[0091] The arrangement of the first pole ear 113 will increase the thickness of the location. In order to reduce the thickness overlap between the first pole ear 113 and the first ceramic layer 1312, the first ceramic layer 1312 is divided into two regions arranged in sequence along the width direction of the first diaphragm 13a, namely, the first region 1312a and the second region 1312b. When viewed along the thickness direction of the first diaphragm 13a, part of the first pole ear 113 overlaps part of the first region 1312a, and the thickness H of the first region 1312a is 1 No greater than the thickness H of the second region 1312b 2 .
[0092] In some embodiments, the thickness H of the first region 1312a is 1 is 0, that is, no ceramic layer is provided in the first diaphragm 13a corresponding to the first region 1312a. 1 / H 2 =0, thereby further reducing the thickness at the position of the first electrode tab 113 after winding.
[0093] In some embodiments, 0<H 1 / H 2 ≤1, in this case, a ceramic layer is provided in the first region 1312a, which can enhance the strength of the first diaphragm 13a near the first pole tab 113 to a certain extent and improve the electrolyte infiltration near the first pole tab 113, but H 1 No more than H 2 , so as to reduce the thickness overlap between the first electrode tab 113 and the first ceramic layer 1312 , and reduce the loss of volume energy density of the secondary battery 100 .
[0094] In some embodiments, H 1 =H 2 It can be understood that when the thickness H of the first region 1312a is1 Equal to the thickness H of the second region 1312b 2 When the first ceramic layer 1312 is coated, it is easy to form the first region 1312a and the second region 1312b by coating at the same time.
[0095] In some embodiments, 0.2≤H 1 / H 2 ≤0.5. When H 1 / H 2 ≥0.2, the ceramic layer material disposed in the first region 1312a has a certain thickness, which can enhance the strength of the first diaphragm 13a near the first pole tab 113 and improve the electrolyte infiltration near the first pole tab 113; when H 1 / H 2 ≤0.5, the first region 1312a and the second region 1312b have a certain thickness difference, which reduces the excessive thickness of the first electrode tab 113 caused by the superposition of the thickness of the first electrode tab 113 and the ceramic layer, thereby reducing the loss of volume energy density of the secondary battery 100.
[0096] The ceramic layer material has good mechanical strength, high hardness and compressive resistance, which is conducive to preventing the first diaphragm 13a from being punctured by impurities such as particles and powder, thereby improving the safety of the secondary battery 100. The provision of the first ceramic layer 1312 is conducive to improving the mechanical strength of the first portion 131 close to the winding center of the winding structure, so that the first portion 131 is not easily punctured, thereby reducing the possibility of short circuit caused by direct contact between the first pole piece 11 and the second pole piece 12, and improving the Hipot test results and K value.
[0097] In addition, the ceramic material in the first ceramic layer 1312 has pores, which is conducive to storing electrolyte and guiding the flow of electrolyte. The closer to the winding center of the electrode assembly 10, the greater the winding pressure, the less likely it is for the electrolyte to infiltrate, and the electrolyte near the winding center is easily squeezed out during the pressure of the electrode assembly 10, resulting in insufficient electrolyte near the winding center. By providing the first ceramic layer 1312 in the first part 131, the electrolyte is easy to infiltrate into the winding center, reducing the situation of poor electrolyte infiltration or swelling near the winding center, thereby reducing the lithium deposition of the first pole piece 11 and the second pole piece 12.
[0098] In some embodiments, the first base film 1311 and the second base film 1321 are made of the same material and have the same thickness, which is beneficial to the production and preparation of the first diaphragm 13 a.
[0099] See also Figure 7 , Figure 7 yes Figure 6The thickness of the first region 1312a is H. 1 , the thickness of the second region 1312b is H 2 ,exist Figure 7 In the embodiment shown, H 1 <H 2 This is beneficial to reducing the loss of volume energy density of the secondary battery 100 caused by the overlapping thickness of the first electrode tab 113 and the first region 1312a.
[0100] In some embodiments, the thickness H of the second ceramic layer 1322 is 3 The thickness H of the second region 1312b is 2 The ratio range is 1.2≤H 2 / H 3 ≤10. By making H 2 / H 3 Within the above range, the first ceramic layer 1312 can have a certain thickness to provide the first part 131 with sufficient puncture resistance and improve the problem of insufficient electrolyte in the winding center, and the thickness difference between the first part 131 and the second part 132 will not be too large, so as to reduce the impact on the volume energy density of the secondary battery 100 and the flatness of the electrode assembly 10.
[0101] In some embodiments, the thickness H of the second ceramic layer 1322 is 3 The thickness H of the second region 1312b is 2 The preferred ratio range is 1.5≤H 2 / H 3 ≤5. When H 2 / H 3 Within the above range, the puncture resistance of the first portion 131 can be further improved and the electrolyte shortage problem in the winding center can be improved, while the volume energy density of the secondary battery 100 and the flatness of the electrode assembly 10 can be taken into consideration.
[0102] In some embodiments, H 1 =H 3 By configuring in this way, the manufacturing process of the first diaphragm 13a can be simplified.
[0103] See also Figure 6 and Figure 7 In some embodiments, along the width direction of the first pole piece 11, the width of the first region 1312a is W 1 , 10mm≤W 1 ≤30mm. For example, W 1It can be 10 mm, 12 mm, 15 mm, 18 mm, 20 mm, 22 mm, 25 mm, 28 mm or 30 mm. For example, the width of the first diaphragm 13a is 80 mm, the width of the first ceramic layer 1312 is equal to the width of the first diaphragm 13a, and the width W of the first region 1312a is 1 The width of the second area 1312b is 20mm, and the width of the second area 1312b is 60mm.
[0104] When the width of the first region 1312a is too large, the width of the second region 1312b will become narrower, and the thickened portion will become narrower, which will reduce the thickened area of the first portion 131, which is not conducive to reducing the risk of the first portion 131 being pierced. If the width of the first region 1312a is too small, the first pole ear 113 is easy to overlap with the second region 1312b, thereby increasing the thickness of the wound electrode assembly 10 and causing a loss in the volume energy density of the secondary battery 100. Satisfying 10mm≤W 1 When the thickness of the electrode assembly 10 is ≤30 mm, the second region 1312 b can be increased as much as possible without increasing the thickness of the electrode assembly 10 , thereby reducing the risk of the first portion 131 being punctured and improving the safety performance of the secondary battery 100 .
[0105] In some embodiments, 2 μm ≤ H 2 ≤10μm; 0.3μm≤H 3 ≤1.5μm. When H 2 and H 3 When the above range is met, the structural strength of the first portion 131 and the second portion 132 can be improved while the thickness of the first portion 131 and the second portion 132 does not increase too much, thereby reducing the impact on the volume energy density of the secondary battery 100 .
[0106] In some embodiments, 2 μm ≤ H 2 ≤3 μm. Within this range, the influence of the thickness of the first ceramic layer 1312 and the thickness of the electrode assembly 10 after winding can be reduced, thereby reducing the volume energy density loss of the secondary battery 100.
[0107] See also Figure 2 and Figure 4 In some embodiments, the first diaphragm 13a includes a multi-fold diaphragm segment 13c, and the first portion 131 includes N-fold diaphragm segments 13c located at the winding starting end 10a of the winding structure, 1≤N≤15.
[0108] The winding structure is subjected to a greater winding pressure at a position near the winding center. By thickening the thickness of the first ceramic layer 1312 at the first part 131 near the winding center, the puncture resistance and electrolyte infiltration degree of the first diaphragm 13a near the winding center of the electrode assembly 10 are improved, so that the first diaphragm 13a near the winding center of the electrode assembly 10 is not easily punctured, and the winding center is not easily lithium deposited, thereby improving the cycle performance of the secondary battery 100. If N is too small, the first part 131 is not enough to improve the overall strength of the first diaphragm 13a, the improvement of the puncture resistance of the first diaphragm 13a is small, and the electrolyte is difficult to infiltrate to the middle position of the electrode assembly 10; if N is too large, the first part 131 has a greater impact on the overall thickness of the electrode assembly 10, and the volume energy density of the secondary battery 100 is greatly lost.
[0109] See also Figure 2 and Figure 4 In some embodiments, the electrode assembly 10 includes a main body region 101 and two corner regions 102, and the main body region 101 is located between the two corner regions 102. The boundary line P between the main body region 101 and the corner region 102 1 like Figure 2 The electrode assembly 10 includes a straight section 1011 and a curved section 1021, the straight section 1011 and the curved section 1021 are connected in sequence, the area where the straight section 1011 is located is the main area 101, and the area where the curved section 1021 is located is the corner area 102. The boundary line P between two adjacent folded membrane sections 13c is 2 The folded membrane section 13c is located at the middle position of the curved section 1021 along the winding direction R. It can be understood that the folded membrane section 13c located at the winding tail end 10b of the winding structure is the distance from the tail end 10b to the dividing line P. 2 The part between.
[0110] In some embodiments, 2≤N≤7. Within this range, the overall thickness of the electrode assembly 10 can be further reduced while improving the wetting effect of the electrolyte on the electrode assembly 10 and reducing the risk of lithium plating.
[0111] In some embodiments, the first diaphragm 13a further includes a first adhesive layer 133, and the first adhesive layer 133 is disposed on a side of the first ceramic layer 1312 away from the first base film 1311, and / or, the first adhesive layer 133 is disposed on a side of the second ceramic layer 1322 away from the second base film 1321, and / or, the first adhesive layer 133 is disposed on a side of the first base film 1311 away from the first ceramic layer 1312, and / or, the first adhesive layer 133 is disposed on a side of the second base film 1321 away from the second ceramic layer 1322. Figure 8The first adhesive layer 133 is disposed on the side of the first ceramic layer 1312 away from the first base film 1311 and the side of the first base film 1311 away from the first ceramic layer 1312. After the electrode assembly 10 is wound to form a wound structure, the first adhesive layer 133 can increase the bonding strength between the first diaphragm 13a and the first pole piece 11 and the second pole piece 12, so that the first diaphragm 13a is not easy to be folded, reducing the risk of contact between the first pole piece 11 and the second pole piece 12, and improving the safety of the battery.
[0112] In some embodiments, the first adhesive layer 133 includes a binder, and the material of the binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyvinyl alcohol, sodium carboxymethyl cellulose, and acrylate.
[0113] See also Fig. 9 and Fig.10 , Fig.10 yes Fig. 9 Cross-sectional view along the thickness direction of the first diaphragm 13a. In some embodiments, along the width direction of the first diaphragm 13a, the first diaphragm 13a includes a third portion 134 and a fourth portion 135 arranged in sequence, and along the thickness direction of the first diaphragm 13a, a portion of the first electrode tab 113 overlaps a portion of the third portion 134. 2 The boundary between the third part 134 and the fourth part 135
[0114] The third portion 134 includes a third base film 1341, and the fourth portion 135 includes a fourth ceramic layer 1352 and a fourth base film 1351 stacked in the thickness direction of the first diaphragm 13a. The thickness of the third portion 134 is H 4 , the thickness of the fourth portion 135 is H 5 , H 4 <H 5 .
[0115] After the fourth portion 135 is provided with the fourth ceramic layer 1352, the thickness of the fourth portion 135 is thicker than that of the third portion 134, and the fourth ceramic layer 1352 has good mechanical strength, which is beneficial to reduce the possibility of the first diaphragm 13a being punctured and the risk of short circuit caused by direct contact between the first pole piece 11 and the second pole piece 12. In addition, by limiting H 4 <H 5 , reducing the thickness overlap at the position of the first electrode tab 113 , thereby reducing the thickness of the electrode assembly 10 after winding, which is beneficial to reducing the loss of volume energy density of the secondary battery 100 .
[0116] In some embodiments, the materials of the third base film 1341 and the fourth base film 1351 independently include at least one of polyethylene, polypropylene, polyimide, polyamide, polysulfone, polyacrylonitrile, polyester, cellulose, polyphenylene sulfide, polyacrylate, polyethylene terephthalate, polyphenylamide, polyarylethersulfoneketone, aramid or aromatic sulfone. In some embodiments, the third base film 1341 and the fourth base film 1351 are made of the same material and have the same thickness, which is conducive to the production and preparation of the first diaphragm 13a.
[0117] In some embodiments, along the width direction of the first pole piece 11, the width of the third portion 134 is W 2 , 10mm≤W 2 ≤30mm. For example, W 2 It can be 10mm, 12mm, 15mm, 18mm, 20mm, 22mm, 25mm, 28mm or 30mm.
[0118] The width W of the third portion 134 2 If the width of the third portion 134 is too large, the width of the fourth portion 135 will become narrower, that is, the thickened portion will become narrower, which will reduce the area where the strength of the first diaphragm 13a is increased, which is not conducive to reducing the risk of the first diaphragm 13a being punctured. If the width of the third portion 134 is too small, the first pole ear 113 is easy to overlap with the fourth ceramic layer 1352 of the fourth portion 135, thereby increasing the thickness of the wound electrode assembly 10 and causing a loss in the volume energy density of the secondary battery 100. Satisfying 10mm≤W 2 When the thickness of the electrode assembly 10 is ≤30 mm, the fourth portion 135 can be increased as much as possible without increasing the thickness of the electrode assembly 10 , thereby reducing the risk of the first portion 131 being punctured and improving the safety performance of the secondary battery 100 .
[0119] See also Fig.11 In some embodiments, the third portion 134 further includes a third ceramic layer 1342. The third ceramic layer 1342 and the third base film 1341 are stacked along the thickness direction of the first diaphragm 13a. The thickness of the third ceramic layer 1342 is H. 6 , the thickness of the fourth ceramic layer 1352 is H 7 , 0.2≤H 6 / H 7 ≤0.5.
[0120] The third ceramic layer 1342 is provided to enhance the structural strength of the first diaphragm 13a, so that the third portion 134 is not easily punctured, and can improve the electrolyte infiltration near the first tab 113. And satisfy H 6 / H 7When ≤0.5, the thickness overlap of the first electrode tab 113 and the third ceramic layer 1342 can be reduced, and the thickness increase of the electrode assembly 10 after winding can be reduced, which is beneficial to reducing the volume energy density loss of the secondary battery 100.
[0121] In some embodiments, 2 μm ≤ H 7 ≤10μm; 0.3μm≤H 6 When the above range is met, the thickness of the third part 134 and the fourth part 135 is not likely to increase too much while improving the structural strength of the third part 134 and the fourth part 135 , thereby reducing the impact on the volume energy density of the secondary battery 100 .
[0122] In some embodiments, 2 μm ≤ H 7 ≤3μm. Satisfy 2μm≤H 7 When the thickness of the fourth ceramic layer 1352 is less than or equal to 3 μm, the thickness of the fourth ceramic layer 1352 can be greater than that of the third ceramic layer 1342 , while the thickness of the fourth ceramic layer 1352 is not easily too large, thereby reducing the impact on the overall thickness of the electrode assembly 10 .
[0123] See also Fig.12 , an embodiment of the present application further provides an electric device 1000, which includes the secondary battery 100 in any of the above embodiments.
[0124] By increasing the thickness of a part of the first diaphragm 13a, the first diaphragm 13a is not easily punctured, so that the first pole piece 11 is not easily short-circuited with the second pole piece 12, thereby improving the safety of the secondary battery 100 and further improving the safety of the electrical device 1000.
[0125] In some embodiments, the electrical device 1000 may be a mobile phone, a laptop computer, a tablet computer, a drone, an electric tool, an electric toy, a game console, a video recorder, a portable recorder, a radio, or a smart watch, etc., which are not listed one by one here.
[0126] In some embodiments, the power-consuming device 1000 further includes a device body 200, and the secondary battery 100 is installed in the device body 200. Since the power-consuming device 1000 adopts the technical solution of the secondary battery 100 in any of the above embodiments, it has at least the beneficial effects brought by the technical solution of any of the above embodiments of the secondary battery 100, which will not be described one by one here.
[0127] In order to verify the influence of different settings of the first separator 13a on the performance of the secondary battery 100, the inventors conducted the following experiments:
[0128] 1.Hipot test:
[0129] The first pole piece 11, the first diaphragm 13a and the second pole piece 12 are stacked in sequence and the electrode assembly 10 is obtained through a winding process. The leakage current generated by the electrode assembly 10 under the test high voltage output by the high-voltage machine is compared with the set judgment current. If the detected leakage current value is greater than or equal to the preset value, the product under test is judged to have passed the test (OK); if the detected leakage current value is less than the preset value, the test voltage is instantly cut off and the product under test is judged to have failed the test (NG). The preset value of the judgment current in this experiment is 5mΩ. When the leakage current value is lower than 5mΩ, it means that it can be turned on but the resistance is too small, there is a short circuit point, and it is judged to be NG; when the leakage current value is greater than or equal to 5mΩ, it is judged to be OK. Take 1000 electrode assemblies 10 for each group of comparative examples and each group of embodiments for testing, and record the pass rate of the Hipot test of each group. The pass rate of the Hipot test is the ratio of the number of electrode assemblies 10 that pass the test in the same group to the total number of electrode assemblies 10 tested in the group. For example, the number of electrode assemblies 10 that pass the test in the same group is X 1 , 1000 electrode assemblies are tested in each group, and the pass rate of the Hipot test is recorded as "X 1 / 1000”.
[0130] 2. K value test (voltage drop per unit time test):
[0131] The electrode assembly 10 is assembled into a secondary battery 100. When the secondary battery 100 stores 60% of the power, its voltage is measured at 25±5°C and recorded as the first voltage. After standing for 48 hours, its voltage is measured again and recorded as the second voltage. The voltage drop per unit time is recorded as K, where K=(first voltage-second voltage) / standing time. 1000 secondary batteries 100 are tested for each comparative example and each example. A K value less than 0.006mV / h is judged to have passed the K value test (OK), and a K value greater than or equal to 0.006mV / h is judged to have failed the K value test (NG). 1000 secondary batteries 100 are tested for each comparative example and each example, and the K value test pass rate of each group is recorded. The K value test pass rate is the ratio of the number of secondary batteries 100 in the same group that pass the test to the total number of secondary batteries 100 in the group. For example, the number of secondary batteries 100 in the same group that pass the test is X. 2 , each group tests 1000 secondary batteries, and the K value test pass rate is recorded as "X 2 / 1000”.
[0132] 3. Test on the probability of lithium deposition:
[0133] Twenty secondary batteries 100 were taken for testing in each group of comparative examples and each group of examples.
[0134] The secondary battery 100 is placed in a test environment at a temperature of 25°C for 30 minutes, and is step-charged to 4.5V according to the following charging steps:
[0135] ①5C constant current charging to 4.23V, constant voltage charging to 4C;
[0136] ②4C constant current charging to 4.3V, constant voltage charging to 3C;
[0137] ③3C constant current charging to 4.5V, constant voltage charging to 2C;
[0138] ④2C constant current charging to 4.5V, constant voltage charging cut-off current to 0.05C;
[0139] After standing for 10 minutes, discharge according to the following steps:
[0140] 0.2C constant current discharge to 3V.
[0141] The above charge and discharge process is one cycle. After repeating 1200 cycles, when the secondary battery 100 is in a fully charged state (the designed maximum voltage of the secondary battery 100 is 4.5V), the secondary battery 100 is disassembled to obtain the anode electrode sheet. The surface of the anode electrode sheet opposite to the first area 1312a, the second area 1312b, the third part 134 or the fourth part 135 is observed. The non-lithium deposited area is black, and the lithium deposited area is grayish white. If the lithium deposited area on the surface of the anode electrode sheet is greater than or equal to 1mm 2 , it is determined to be lithium deposition and the test fails, otherwise it is considered to pass the test, and the probability of lithium deposition in each group is recorded. The probability of lithium deposition is the ratio of the number of secondary batteries 100 in the same group that have lithium deposition to the total number of secondary batteries 100 in the group. For example, the number of secondary batteries 100 in the same group that have lithium deposition is X. 3 , each group tests 20 secondary batteries 100, then the probability of lithium deposition is recorded as "X 3 / 20”.
[0142] 4. Volume energy density test:
[0143] The volume energy density of the secondary battery 100 is calculated, and the volume energy density = the first discharge cycle capacity / (the length of the secondary battery × the width of the secondary battery × the thickness). The volume energy density of the 20 secondary batteries 1000 in the same group is averaged and recorded in Table 1 and Table 2.
[0144] 5.H 1 , H 2 , H 3 , H 4 and H 5 Measurements:
[0145] The first diaphragm 13a is peeled off from the electrode, and the first diaphragm 13a at the first area 1312a is cut into 2cm×2cm diaphragm samples. The diaphragm samples are pasted onto the conductive adhesive and placed on the SEM (Scanning Electron Microscope) sample stage for testing. The H 1 The same test method is used to measure the first diaphragm 13a at the second area 1312b, the first diaphragm 13a at the second part 132, the first diaphragm 13a at the third part 134 and the first diaphragm 13a at the fourth part 135 to obtain H 2 , H 3 , H 4 and H 5 .
[0146] 6.W 1 , W 2 Measurements:
[0147] Use a micrometer to measure W 1 and W 2 .
[0148] Comparative Examples and Examples
[0149] Preparation of Secondary Battery 100:
[0150] (1) Preparation of cathode electrode:
[0151] The cathode active material is lithium cobalt oxide, the cathode conductive agent is acetylene black, and the cathode binder is polyvinylidene fluoride (PVDF, with a weight average molecular weight of 5×10 5 ) are mixed in a mass ratio of 94:3:3, N-methylpyrrolidone (NMP) is added as a solvent, and the cathode slurry is stirred under the action of a vacuum mixer until the solid content is 75wt% and the system is uniform. An aluminum foil with a thickness of 8μm is selected as the cathode current collector, and a foam glue is pasted at a preset position on one surface of the cathode current collector aluminum foil along its thickness direction. The cathode slurry is evenly coated on one surface of the cathode current collector aluminum foil along its thickness direction, and dried at 110°C to obtain a cathode pole piece with a single-sided cathode active material layer (thickness 80μm). Afterwards, the above steps are repeated on the other surface of the aluminum foil along its thickness direction to obtain a cathode pole piece with a double-sided cathode active material layer. Then the previously pasted foam glue is torn off to produce an empty aluminum foil area for welding the cathode pole ear.
[0152] (2) Preparation of anode electrode
[0153] The anode active material graphite powder, silicon powder, conductive agent conductive carbon black (Sμper P), and binder styrene butadiene rubber (SBR) are mixed in a weight ratio of 67.5:30:1:1.5, and then deionized water is added as a solvent to prepare an anode slurry with a solid content of 50wt%, and stirred evenly. A copper foil with a thickness of 5μm is selected as the anode current collector. The anode slurry is evenly coated on one surface of the anode current collector copper foil along its thickness direction, and dried at 90°C to obtain a single-sided anode pole piece. After the above steps are completed, the single-sided coating of the anode pole piece has been completed. Afterwards, the above steps are repeated on the other surface of the anode pole piece along its thickness direction to obtain an anode pole piece coated with a double-sided anode active material layer.
[0154] (3) Preparation of diaphragm 13
[0155] ① Preparation of the first diaphragm 13a: When preparing the first diaphragm 13a of the comparative example and the embodiment shown in Table 1, a first base film 1311 and a second base film 1321 with a thickness of 4.5 μm and a width of 80 mm are taken, and a first ceramic layer 1312 is coated on the first base film 1311 by gravure coating, and a second ceramic layer 1322 is coated on the second base film 1321 to form a first part 131 and a second part 132 distributed along the length direction of the first diaphragm 13a. The parameters of the first part 131 and the second part 132 are shown in Table 1 below.
[0156] When preparing the first diaphragm 13a of the comparative example and the embodiment shown in Table 2, the third ceramic layer 1342 is coated on the third base film 1341 by gravure coating, and the fourth ceramic layer 1352 is coated on the fourth base film 1351 to form the third part 134 and the fourth part 135 distributed in sequence along the width direction of the first diaphragm 13a. The various parameters of the third part 134 and the fourth part 135 are shown in Table 2 below.
[0157] ② The preparation method of the second diaphragm 13b is the same as the preparation method of the first diaphragm 13a.
[0158] (4) Preparation of electrolyte
[0159] In a dry argon atmosphere, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a mass ratio of 30:50:20 to obtain an organic solution, and then lithium hexafluorophosphate was added to the organic solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.
[0160] (5) Assembly of Secondary Battery 100
[0161] Ultrasonic welding is used to weld aluminum pole ears on the empty aluminum foil area preset for welding cathode pole ears to obtain cathode pole sheets welded with cathode pole ears; ultrasonic welding is used to weld nickel pole ears on the empty copper foil area preset for welding anode pole ears to obtain anode pole sheets welded with anode pole ears. The first diaphragm 13a prepared above, the cathode pole sheet welded with cathode pole ears, the second diaphragm 13b, and the anode pole sheet welded with anode pole ears are stacked in sequence and wound to obtain the electrode assembly 10. In Table 1, the cathode pole ear and the anode pole ear are located on the side where the first area 1312a of the electrode assembly 10 is located. In Table 2, the cathode pole ear and the anode pole ear are located on the side where the third part 134 of the electrode assembly 10 is located. The electrode assembly 10 obtained by winding includes 15 layers, and the total number of folds is 30.
[0162] The electrode assembly 10 is placed in an aluminum-plastic film packaging bag, and the cathode tab and the anode tab are extended from the top seal edge of the packaging bag. After dehydration at 80° C., the electrolyte is injected and the packaging bag is sealed.
[0163] The parameter control and test results of various embodiments and comparative examples are shown in Table 1 and Table 2.
[0164] Table 1
[0165]
[0166]
[0167]
[0168]
[0169] From the comparison of the experimental data of Comparative Example 1-1 and Comparative Example 1-2 to Comparative Example 1-6 and Example 1-1 to Example 1-33 in Table 1, it can be seen that the provision of the first ceramic layer 1312 and the second ceramic layer 1322 in the electrode assembly 10 can significantly improve the Hipot test pass rate and the K value test pass rate, and reduce the probability of lithium deposition in the first region 1312a and the second region 1312b. This is because the provision of the ceramic layer improves the mechanical strength of the first diaphragm 13a, making the first diaphragm 13a not easily punctured by falling particles or carbon powder, and the ceramic layer has a certain porosity, which is beneficial to improving the infiltration and storage of the electrolyte, and is beneficial to reducing the probability of lithium deposition in the first region 1312a and the second region 1312b. From the experimental data of Comparative Example 1-2, Comparative Example 1-3 and Example 1-1 to Example 1-7, it can be seen that when the thickness H of the second region 1312b 2 <2μm, the Hipot test pass rate and the K value test pass rate are still not ideal, and the probability of lithium deposition in the first region 1312a and the second region 1312b is still high; and when H 2When the volume energy density of the secondary battery 100 is greater than 10 μm, the loss of the volume energy density of the secondary battery 100 is more serious. 2 ≤10μm, a higher Hipot test pass rate and K value test pass rate can be obtained, the probability of lithium deposition in the first area 1312a and the second area 1312b is low, and a higher volume energy density can be taken into account. 2 ≤3μm. From the comparison of the experimental data of Comparative Example 1-4 and Example 1-1, Example 1-8 to Example 1-14, it can be seen that H 1 / H 2 >1, the volume energy density of the secondary battery 100 has a certain loss. In order to make the secondary battery 100 have a higher volume energy density, the thickness H of the first region 1312a overlapping with the first electrode tab 113 is limited. 1 Less than or equal to the thickness H of the second region 1312b 2 , that is, 0≤H 1 / H 2 ≤1, where H 1 / H 2 =0, the first region 1312a is not provided with the first ceramic layer 1312, and the volume energy density of the secondary battery 100 is relatively high at this time, but the probability of lithium deposition in the first region 1312a is increased. This is because the first region 1312a is not provided with a ceramic layer, resulting in poor electrolyte infiltration in the first region 1312a. In order to take into account both the electrolyte infiltration in the first region 1312a and the volume energy density of the secondary battery 100, it is preferred that 0.2≤H 1 / H 2 ≤0.5. From the comparison of the experimental data of Comparative Examples 1-5, Comparative Examples 1-6 and Examples 1-1, Examples 1-15 to Examples 1-21, it can be seen that when H 2 / H 3 =1, that is, H 2 =H 3 When H, the thickness of the second portion 132 is equal to the thickness of the second region 1312b, and the volume energy density loss of the secondary battery 100 is relatively serious; 2 / H 3 When H>10, the difference between the thickness of the second portion 132 and the thickness of the second region 1312b is large, and the thickness of the second portion 132 is small, resulting in a low Hipot test pass rate and a low K value test pass rate. In order to take into account a higher volume energy density and a higher Hipot test pass rate and a higher K value test pass rate, the limit is 1.2≤H 2 / H 3 ≤10; further, preferably 1.5≤H 2 / H 3≤5. From the comparison of the experimental data of Example 1-1 and Example 1-22 to Example 1-25, it can be seen that when the width W of the first region 1312a is 1 When W is less than 10 mm, the first electrode tab 113 has the risk of overlapping with the second region 1312 b, which may cause the first electrode tab 113 to overlap with the thickness of the second region 1312 b having a larger thickness, resulting in a loss of volume energy density of the secondary battery 100. 1 When W>30mm, the width of the thicker second region 1312b is small, resulting in a lower Hipot test pass rate and a lower K value test pass rate. In order to take into account both a higher volume energy density and a higher Hipot test pass rate and a higher K value test pass rate, the limit is 10mm≤W 1 ≤30mm. From the comparison of the experimental data of Example 1-1 and Example 1-26 to Example 1-33, it can be seen that when the fold number N of the first part 131 is greater than 15, the volume energy density of the secondary battery 100 is lower due to the large number of thickened areas of the ceramic layer; when the fold number N of the first part 131 is too small, the Hipot test pass rate and the K value test pass rate are lower. In order to take into account both the higher volume energy density and the higher Hipot test pass rate and the K value test pass rate, the limit is 1≤N≤15; further, 2≤N≤7 is preferred.
[0170] Table 2
[0171]
[0172]
[0173] From the comparison of the experimental data of Comparative Example 2-1, Comparative Example 2-2 and Example 1-1 in Table 2, it can be seen that compared with H 4 <H 5 In the case of H 4 >H 5 or H 4 =H 5 When the thickness of the third portion 134 overlapping the first electrode tab 113 is large, the thickness of the first electrode tab 113 overlaps with the thickness of the third portion 134, resulting in an increase in the thickness of the secondary battery 100, thereby making the volume energy density of the secondary battery 100 low. By comparing the experimental data of Comparative Examples 2-3, Comparative Examples 2-4 and Examples 2-1 to 2-7, it can be seen that when the thickness H of the fourth ceramic layer 1352 is 7When the thickness of the fourth ceramic layer 1352 is smaller than 2 μm, the pass rate of the Hipot test and the pass rate of the K value test are lower, and the probability of lithium deposition in the fourth part 135 is higher. This is because when the thickness of the fourth ceramic layer 1352 is smaller, the puncture resistance of the first diaphragm 13a is lower, and particles or carbon powder are easy to cause the first diaphragm 13a to be punctured, resulting in a micro short circuit, which leads to a lower pass rate of the Hipot test and the pass rate of the K value test, and because the ceramic layer is thin, the fourth part 135 is prone to poor electrolyte infiltration, resulting in a higher probability of lithium deposition in the fourth part 135; when the thickness of the fourth ceramic layer 1352 is smaller than 2 μm, the puncture resistance of the first diaphragm 13a is lower, and particles or carbon powder are easy to cause the first diaphragm 13a to be punctured, resulting in a micro short circuit, which leads to a lower pass rate of the Hipot test and the pass rate of the K value test, and because the ceramic layer is thin, the fourth part 135 is prone to poor electrolyte infiltration, which leads to a higher probability of lithium deposition in the fourth part 135; 7 When the thickness of the ceramic layer is greater than 10 μm, the thickness of the secondary battery 100 increases due to the increase in the thickness of the ceramic layer, resulting in a lower volume energy density of the secondary battery 100. Therefore, in order to take into account the higher Hipot test pass rate and the K value test pass rate, the fourth part 135 has a lower probability of lithium deposition and a higher volume energy density, and limits 2 μm ≤ H 7 ≤10μm; further, preferably 2μm≤H 7 ≤3μm. From the comparison of the experimental data of Examples 2-8 to 2-12, it can be seen that when the thickness H of the third ceramic layer 1342 is 6 and the thickness H of the fourth ceramic layer 1352 7 The ratio H 6 / H 7 <0.2, the thickness of the third ceramic layer 1342 is relatively low, and the probability of lithium deposition in the third portion 134 is relatively high; when H 6 / H 7 When H>0.5, the volume energy density of the secondary battery 100 is reduced. Therefore, in order to take into account the lower probability of lithium deposition in the third part 134 and the higher volume energy density of the secondary battery 100, the limit is 0.2≤H 6 / H 7 ≤0.5. From the comparison of the experimental data of Example 2-10 and Example 2-13 to Example 2-16, it can be seen that when the width W of the third portion 134 is 2 When W is less than 10 mm, the first electrode tab 113 has the risk of overlapping with the fourth portion 135, which may cause the first electrode tab 113 to overlap with the thickness of the fourth portion 135 having a larger thickness, resulting in a loss of volume energy density of the secondary battery 100. 2 When W is greater than 30 mm, the width of the thicker fourth portion 135 is smaller, resulting in lower Hipot test pass rate and K value test pass rate. In order to take into account both higher volume energy density and higher Hipot test pass rate and K value test pass rate, the limit is 10 mm ≤ W 2 ≤30mm.
[0174] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present application and are not intended to be limiting of the present application. As long as they are within the spirit and scope of the present application, appropriate changes and modifications to the above embodiments are within the scope of the present application.
Claims
1. A secondary battery, characterized in that: The secondary battery comprises an electrode assembly, wherein the electrode assembly comprises a first electrode sheet, a second electrode sheet and a first diaphragm, wherein the first electrode sheet, the first diaphragm and the second electrode sheet are sequentially stacked to form a winding structure; along the winding direction of the first diaphragm, the first diaphragm comprises a first portion and a second portion which are sequentially arranged, and compared with the second portion, the first portion is closer to the winding start end of the winding structure; Along the thickness direction of the first diaphragm, the first portion includes a first ceramic layer and a first base film which are stacked, and the second portion includes a second ceramic layer and a second base film which are stacked; The first pole piece includes a first current collector and a first pole ear, wherein the first pole ear is connected to the first current collector and extends from one side in the width direction of the first current collector; the first ceramic layer includes a first region and a second region sequentially arranged along the width direction of the first diaphragm; along the width direction of the first diaphragm, a portion of the first pole ear overlaps with at least a portion of the first region; The thickness of the first region is H1, the thickness of the second region is H2, the thickness of the second ceramic layer is H3, 2 μm≤H2≤10 μm, 0≤H1 / H2≤1, and 1.2≤H2 / H3≤10.
2. The secondary battery according to claim 1, wherein: 1.5≤H2 / H3≤5.
3. The secondary battery according to claim 1 or 2, characterized in that: 0.2≤H1 / H2≤0.
5.
4. The secondary battery according to claim 1, wherein: 0.3μm≤H3≤1.5μm.
5. The secondary battery according to claim 4, characterized in that: 2μm≤H2≤3μm.
6. The secondary battery according to claim 1, wherein: The first membrane includes a multi-fold membrane segment, and the first portion includes N folds of the membrane segment located at the starting end of the winding, 1≤N≤15.
7. The secondary battery according to claim 6, characterized in that: 2≤N≤7。 8. The secondary battery according to claim 1, wherein: Along the width direction of the first pole piece, the width of the first region is W1, 10 mm≤W1≤30 mm.
9. The secondary battery according to claim 1, wherein: The materials of the first ceramic layer and the second ceramic layer each independently include at least one of aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, barium titanate, and boehmite.
10. A secondary battery, characterized in that: The secondary battery comprises an electrode assembly, the electrode assembly comprises a first electrode sheet, a second electrode sheet and a first separator, the first electrode sheet, the first separator and the second electrode sheet are sequentially stacked to form a winding structure; the first electrode sheet comprises a first current collector and a first electrode ear, the first electrode ear is connected to the first current collector and extends from one side in the width direction of the first current collector; along the width direction of the first separator, the first separator comprises a third part and a fourth part arranged in sequence; when observed along the thickness direction of the first separator, part of the first electrode ear overlaps part of the third part; The third part includes a third base film, and the fourth part includes a fourth ceramic layer and a fourth base film stacked along the thickness direction of the first diaphragm; the thickness of the third part is H4, the thickness of the fourth part is H5, H4<H5; the thickness of the fourth ceramic layer is H7, 2μm≤H7≤10μm.
11. The secondary battery according to claim 10, characterized in that: Along the width direction of the first pole piece, the width of the third portion is W2, 10mm≤W2≤30mm.
12. The secondary battery according to claim 10 or 11, characterized in that: The third part further includes a third ceramic layer. The third ceramic layer and the third base film are stacked along the thickness direction of the first diaphragm. The thickness of the third ceramic layer is H6, 0.2 μm≤H6 / H7≤0.5 μm.
13. The secondary battery according to claim 12, characterized in that: 0.3μm≤H6≤1.5μm.
14. The secondary battery according to claim 13, characterized in that: 2μm≤H7≤3μm.
15. An electrical device, characterized in that: Comprising the secondary battery according to any one of claims 1 to 14.
Citation Information
Patent Citations
Secondary battery and electric device
CN117977014A
Secondary battery and electronic device
CN118173900A
Single battery and battery module
CN219959320U
Electrochemical apparatus and electronic apparatus
WO2023173331A1
Separator, battery cell, hot-pressing mold, battery, and electric device
WO2024016452A1